2002
DOI: 10.1111/j.2042-7174.2002.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Is 15 per cent very common? Informing people about the risks of medication side effects

Abstract: Objectives — To assess the general public's interpretation of the verbal descriptors for side effect frequency recommended for use in medicine information leaflets by a European Union (EU) guideline, and to examine the extent to which differences in interpretation affect people's perception of risk and their judgments of intention to comply with the prescribed treatment. Method — Two studies used a controlled empirical methodology in which people were presented with a hypothetical, but realistic, scenario abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 16 publications
7
81
1
Order By: Relevance
“…About 47% of subjects were male, which was reported by all trials except in Berry and colleagues (2004) 109 and in the first trial reported in Berry and colleagues (2002). 105 The ethnic background of participants was not reported in any trials. The participants' education status was reported in all trials except Bergus and colleagues.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…About 47% of subjects were male, which was reported by all trials except in Berry and colleagues (2004) 109 and in the first trial reported in Berry and colleagues (2002). 105 The ethnic background of participants was not reported in any trials. The participants' education status was reported in all trials except Bergus and colleagues.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
“…Seven authors (of 10 papers) answered the request for missing data. 34,35,84,87,[103][104][105][109][110][111] Copies of the interventions available (from either the paper or the authors) can be found in Appendix 9.…”
Section: Effectiveness Review Overviewmentioning
confidence: 99%
See 3 more Smart Citations